A discourse analysis of national identity in Nigerian stand-up humour. (June 2020) - Filani, Ibukun
This article explores the comedic construction of national identity in Nigerian stand-up comedy. By national identity, I mean collective perspectives on the sociopolitical and cultural realities of postcolonial Nigeria. While critical discourse analysis provided the framework for interpretation, data was derived from purposively sampled recorded videos of Nigerian stand-up comedians. Such collective perspectives are constructed when a comedian indexes cultural/political events and situations in a monologue. The investigation reveals four identity mapping strategies: performing (non)theatrical identities, using the comedy voice to indicate multiple identities, constructing a trickster identity and constructing a resilient spirit identity. These strategies entail foregrounding assumptions about the Nigerian state and using language in a strategic way to indicate sociopolitical and cultural realities.